1987
DOI: 10.1007/bf02153409
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurement of the posterior coats of the eye and their relation to axial length

Abstract: In 159 eyes with a spherical correction varying from +14.0 to -27.0 diopters, the axial length and thickness of posterior ocular coats were measured ultrasonographically. As proven in experimental studies, retina, choroid, and sclera were resolved in a considerable percentage of cases by combining A- and B-mode techniques of modern ultrasonographic equipment. The presumed close inverse correlation between the axial length of the eye and ocular coat dimensions was confirmed by statistical analysis. These values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Nemeth et al 10 and Guthoff et al 38 reported similar findings in their studies after measuring the thickness of the "posterior ocular coat" (i.e., retina through sclera without measurement of the choroid separately) using ultrasonography. This technique measured the thickness from the retina to the sclera rather than the choroid alone.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Nemeth et al 10 and Guthoff et al 38 reported similar findings in their studies after measuring the thickness of the "posterior ocular coat" (i.e., retina through sclera without measurement of the choroid separately) using ultrasonography. This technique measured the thickness from the retina to the sclera rather than the choroid alone.…”
Section: Discussionmentioning
confidence: 61%
“…There were 53 men and 61 women, and 60 right and 54 left eyes. Distribution by ethnic origin was as follows: 38 …”
Section: Demographic and Clinical Characteristics Of Subjectsmentioning
confidence: 99%
“…Other measurements with scanning laser Doppler flowmeter showed a reduced retinal microcirculation in myopic and glaucomatous eyes [31]. Guthoff et al and Németh et al showed that in healthy persons the thickness of the ocular wall is very closely dependent on the axial length of the eye, and that the volume of the wall of the eye is nearly constant [32]. Choroidal thickness may probably not be an absolute indicator for failure or success of treatment for endophthalmitis, but decreased choroidal thickness can explain unexpected clinical outcomes with poor vision.…”
Section: Discussionmentioning
confidence: 99%
“…Guthoff et al . measured axial length and thickness of the posterior ocular coats ultrasonographically, including the choroid, in 159 eyes with a spherical correction varying from +14.0 to −27.0 diopters 31 . They found a constant tissue volume regardless of the difference in axial length between hyperopic and myopic eyes, suggesting that choroidal thinning in myopia was a function of axial elongation and passive stretch.…”
Section: Discussionmentioning
confidence: 99%